2015
DOI: 10.1155/2015/278591
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Endometrial Glycodelin Expression and Pregnancy Outcome in Cases with Polycystic Ovary Syndrome Treated with Clomiphene Citrate Plus Metformin: A Controlled Study

Abstract: Objective. The purpose of this study was to evaluate the relationship between clomiphene citrate (CC) plus metformin treatment and endometrial glycodelin expression and to then correlate this relationship with pregnancy outcomes. Material and Methods. A total of 30 patients diagnosed with polycystic ovary syndrome (PCOS) according to the Rotterdam criteria constituted our study group. All had been admitted to the gynecology outpatient clinic between June 1, 2011, and January 1, 2012, for infertility treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The decrease of glycodelin in the endometrium and in the serum is associated with increased rate of miscarriage. In PCOS women hyperinsulinemic state decreases the concentrations of circulating glycodelin [ 49 ]. Moreover, hyperinsulinemia may decrease expression of IGF binding protein-1, which is important in adhesion processes of feto-maternal interaction.…”
Section: An Inflammatory Process In Pcos As a Risk Factor For Earlmentioning
confidence: 99%
“…The decrease of glycodelin in the endometrium and in the serum is associated with increased rate of miscarriage. In PCOS women hyperinsulinemic state decreases the concentrations of circulating glycodelin [ 49 ]. Moreover, hyperinsulinemia may decrease expression of IGF binding protein-1, which is important in adhesion processes of feto-maternal interaction.…”
Section: An Inflammatory Process In Pcos As a Risk Factor For Earlmentioning
confidence: 99%
“…Tapia-Pizarro et al (39) found immunostaining for GdA was significantly decreased in endometrial samples from women experienced repeatedly implantation failure. Also, Uysal et al (40) reported that when GdA expression was high in PCOS group, the pregnancy rate was 60% and all pregnancies ended in live births, while in weak expression group, EPL rate was 75% and concluded that endometrial GdA expression is an important predictor of pregnancy outcomes in both PCOS and fertile groups. Lee et al (41) attributed such role of GdA to the findings that GdA interacts by its unique carbohydrate side chains with the cell surface of various cell types in the human fetomaternal interface and modulates their functions and differentiation to permit successful pregnancy, and documented that abnormal GdA levels in the endometrium, uterine flushings, and/or maternal serum correlate with unexplained infertility, early and recurrent pregnancy loss.…”
Section: Discussion:-mentioning
confidence: 99%
“…Adding metformin to treatment cycle protocols for increasing pregnancy rates among patients with PCOS is a matter of debate. In a systematic review, Palomba et al ( 11 ) concluded that infertile patients with PCOS treated with gonadotrophins for in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles, implantation rates seemed improved but pregnancy or live birth rates did not increase by using metformin despite lower rates of ovarian hyperstimulation syndrome (OHSS) and miscarriage ( 11 , 12 ). Specific phenotypes and features of patients with PCOS who will benefit from metformin should be defined before liberally advising metformin to all patients with PCOS.…”
Section: Metforminmentioning
confidence: 99%